2011
DOI: 10.1177/230949901101900211
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Plate Osteosynthesis Using a Locking Compression Plate for Distal Femoral Fractures

Abstract: MIPO using a LCP achieves favourable biological fixation for distal femoral fractures with few complications. Bone grafting is not needed even in cases of metaphyseal comminution. Proper patient selection and preoperative planning are essential to prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 34 publications
4
29
0
4
Order By: Relevance
“…7 Strength under axial compression was better with the LCP system than with the blade plate or nailing, by 34 and 13% respectively, but strength under torsion was reduced. [8][9][10][11][12] The authors observed better distal fixation with the LCP system with loss of distal fixation in only one LCP plate (6%), three blade plates (38%) and eight losses with retrograde intramedullary nailing (100%).…”
Section: Discussionmentioning
confidence: 94%
“…7 Strength under axial compression was better with the LCP system than with the blade plate or nailing, by 34 and 13% respectively, but strength under torsion was reduced. [8][9][10][11][12] The authors observed better distal fixation with the LCP system with loss of distal fixation in only one LCP plate (6%), three blade plates (38%) and eight losses with retrograde intramedullary nailing (100%).…”
Section: Discussionmentioning
confidence: 94%
“…For minimizing those disadvantages, close reduc on and minimal exposure to facilitate the inser on of retrograde intramedullary nail with preserva on of periosteum and fracture hematoma. Newly introduced minimal invasive plate osteosynthesis (MIPO) techniques were successfully applied in complex extra-ar cular fractures and a modified technique en tled Transar cular Approach and Retrograde Plate Osteosynthesis (TARPO) was developed for complex [19][20][21] supracondylar and intercondylar femoral fractures. Since the use of pla ng and nailing technique has modernized, there has been a major improvement in the treatment of distal femur fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of locking compression plate and the minimally invasive plate osteosynthesis (MIPO) technique has proved very effective in the treatment of periprosthetic distal femoral fractures as it maintains reduction and anatomical alignment of the fracture while minimizing soft tissue dissection. [9,12] It provides excellent functional and radiological results with fewer complications. [12] It also eliminates the need for bone grafting.…”
Section: Discussionmentioning
confidence: 99%
“…It preserves the periosteal blood supply and perfusion of the bone as it minimizes soft tissue dissection. [9] The technique is effective in providing excellent clinical, radiological and functional outcomes with fewer complications. [9] J of Evolution of Med and Dent Sci/ eISSN-2278-4802, pISSN-2278-4748/ Vol.…”
Section: Introductionmentioning
confidence: 99%